Protective Effects of Cannabidiol on the Membrane Proteome of UVB-Irradiated Keratinocytes - Sinemyiz Atalay; Agnieszka Gęgotek; Elżbieta Skrzydlewska (MDPI AG, 2021)
Ultraviolet (UV) radiation contained in sunlight disturbs the redox state of skin cells, leading to changes in the structures and functions of macromolecules including components of biological membranes. Cannabidiol (CBD), which accumulates in biomembranes, may be a promising protective antioxidant compound. Accordingly, the aim of this study was to compare the effects of short-term (24 h) and long-term (48 h) CBD application on the proteomic profile of biological membranes in UVB-irradiated keratinocytes. The data obtained show that UVB radiation quantitatively and qualitatively modified cell membrane proteins, with a particular research focus on adducts of proteins with the lipid peroxidation products malondialdehyde (MDA) or 4-hydroxynonenal (4-HNE). CBD application reduced the UVB-enhanced level of these protein adducts. This was particularly notable amongst proteins related to cell proliferation and apoptosis. Moreover, CBD dramatically increased the UVB-induced expression of proteins involved in the regulation of protein translation and cell proliferation (S3a/L13a/L7a ribosomal proteins), the inflammatory response (S100/S100-A6 proteins), and maintenance of redox balance (peroxiredoxin-1, carbonyl reductase 1, and aldo-keto reductase family 1 members). In contrast, CBD effects on the level of 4-HNE-protein adducts involved in the antioxidant response and proteasomal degradation process indicate that CBD may protect keratinocytes in connection with protein catabolism processes or pro-apoptotic action.